Behaving socially with a virtual human role-player in a simulated counseling session. (April 2020) - Hart, John L; Proctor, Michael D
Visual attention is an essential social element in face-to-face conversations between people. The Army is now using virtual environments with virtual human role-players to provide for the development and practice of leader counseling skills. While literature indicates that virtual humans positively impact learning outcomes, this research contributes to the understanding of how people interact with virtual humans. Specifically, the research investigates a person's social behavior toward a virtual human in a simulated counseling session. Utilizing a computer-based training environment, this research tracked visual attention toward and acceptance of a virtual human role-player by 120 military counselors. Behavior moderators included attentional influences on the counselor from the level of expression and full-body or close-up views of the virtual human. Results indicate trainees do practice appropriate social attention when the virtual human is speaking. Results also indicate counselors attended to an active more than a static full-body view indicating there is value in nonverbal communication channels. Switching from a full-body to a close-up view did not result in significant changes of the counselor's visual attention. Further, the research indicates switching views may undermine the perception of a natural interaction. Counselors considered the experience useful. The research suggests study and design considerations to enhance future social skills training environments.